The role of awareness, appreciation, and communication satisfaction in shaping employee engagement: evidence from the organizational health behavior index - Alzuman, Abad; Jaafari, Muath; Ali, Zaiba; Ali, Rahila; Bakadam, Lina Ibrahim (Frontiers in Psychology, 2026)
A healthy organization fosters an environment in which employees feel valued, motivated, and connected to their work. This study examines the relationship between organizational health and employee engagement using the Organizational Health Behavior Index (OHBI) as a multifaceted diagnostic framework, focusing on the joint effects of awareness, appreciation, and communication satisfaction. Data were collected from 7,548 employees across public, private, and semi-government sectors in Saudi Arabia, and Structural Equation Modeling (SEM) was employed to test direct and moderating relationships among the study constructs. Confirmatory Factor Analysis (CFA) demonstrated excellent model fit (CFI = 0.978; RMSEA = 0.048), with all factor loadings exceeding 0.70, supporting convergent and discriminant validity. The results indicate that awareness (β = 0.230), appreciation (β = 0.152), and communication satisfaction (β = 0.070) significantly predict employee engagement (p < 0.001). Moderation analysis further reveals that communication satisfaction strengthens the relationship between awareness and employee engagement (β = 0.082), while slightly attenuating the effect of appreciation (β = −0.027), highlighting its dual role as a contextual moderator. The findings offer actionable insights for enhancing employee engagement and fostering healthier organizational environments across diverse sectors. Although the study is situated within the Saudi Arabian context, the OHBI demonstrates broad applicability across different countries, industries, and organizational settings, providing a practical framework for assessing organizational health and supporting human resource management interventions